A new score based on the International Standards for Neurological Classification of Spinal Cord Injury for integrative evaluation of changes in sensorimotor functions - Grassner, Lukas; Garcia-Ovejero, Daniel; Mach, Orpheus; Lopez-Dolado, Elisa; Vargas-Baquero, Eduardo; Alcobendas-Maestro, Monica; Esclarin, Ana; Sanktjohaneser, Ludwig; Wutte, Christof; Becker, Johannes; Lener, Sara; Hartmann, Sebastian; et al. (Journal of neurotrauma, 2022)
Sensorimotor function of patients with spinal cord injury (SCI) is commonly assessed according to the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI). From the ISNCSCI segmental motor and sensory assessments, upper and lower extremity motor scores (UEMS and LEMS), sum scores of pinprick (PP) and light touch (LT) sensation, the neurological level of injury (NLI) and the classification of lesion severity according to the American Spinal Injury Association Impairment Scale (AIS) grade are derived. Changes of these parameters over time are used widely to evaluate neurological recovery. Evaluating recovery based on a single ISNCSCI scoring or classification variable, however, may misestimate overall recovery. Here, we propose an Integrated Neurological Change Score (INCS) based on the combination of normalized changes between two time points of UEMS, LEMS, and total PP and LT scores. To assess the agreement of INCS with clinical judgment of meaningfulness of neurological changes, changes of ISNCSCI variables between two time points of 88 patients from an independent cohort were rated by 20 clinical experts according to a five-categories Likert Scale. As for individual ISNCSCI variables, neurological change measured by INCS is associated with severity (AIS grade), age, and time since injury, but INCS better reflects clinical judgment about meaningfulness of neurological changes than individual ISNCSCI variables. In addition, INCS is related to changes in functional independence measured by the Spinal Cord Independence Measure (SCIM) in patients with tetraplegia. The INCS may be a useful measure of overall neurological change in clinical studies.
Gesehen am 29.08.2022